Extent of English Language Acquisition in Polytechnic Students: A Study - Arun George, (The Creative Launcher, 2016)
Polytechnic colleges provide skilled supervisors and hence the learners are supposed to acquire both academic knowledge and skill and English language skills. The language skills include Basic Interpersonal Communication Skills (BICS) and Cognitive Academic Language Proficiency (CALP). A study was conducted to find out if the learners have acquired the required English language skills for a successful career. This paper is based on the study conducted in three polytechnics in South Kerala involving the stake-holders of this field. The study investigates the extent of English language acquisition among students enrolled in polytechnic institutions. Recognizing the pivotal role that proficiency in English plays in the globalized world, this research sought to gauge the competence levels and communicative skills of polytechnic students in the English language. The study employed a mixed-method approach, encompassing both quantitative and qualitative data collection techniques, and was conducted across various polytechnic institutions. A stratified sample of students was selected and subjected to a battery of assessments, including standardized language tests, surveys, and interviews. Additionally, academic performance records were examined as ancillary data. The findings revealed a spectrum of proficiency levels, with a noteworthy percentage of students demonstrating only rudimentary command over English. Several variables were found to significantly contribute to this, including the medium of instruction in previous education, socio-economic background, and exposure to the language outside of academia. The study highlights the need for comprehensive language support programmes tailored to the specific needs of polytechnic students, to enhance their English language skills and better equip them for professional opportunities in the global market. It also calls for further research to comprehensively understand the barriers to effective English language acquisition.